2014
DOI: 10.1007/s11325-014-0992-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep, sleep apnea, and neuropsychological function in children with Down syndrome

Abstract: Although SDB is common in children with Down syndrome, it is not a major contributor to their cognitive deficits. Cognitive function is related to the amount of sleep and particularly slow wave sleep. Successful treatment of SDB may improve their attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 29 publications
1
66
0
1
Order By: Relevance
“…A cutoff AHI of ˂ 2/hr was utilized in most of these studies to define the absence of OSA, while 2.0-4.9/hr is often used to define mild OSA, 5.0-9.9 to define moderate OSA, and ˃10/hr to define severe OSA. Descriptively, across these child studies 21.5% of children had mild OSA (95% CI: 16.7 to 26.7), 20.3% moderate OSA (17.3 to 23.5), and 30.4% had severe OSA (20.5 to 41.2) [3], [6], [59], [62], [63], [65], [66], [68], [70], [76], [77]. All but two of these 11 child studies used an AHI cutoff of 2/hr for diagnosing OSA [11], [76].…”
Section: Prevalence Of Osa and Potential Moderatorsmentioning
confidence: 92%
“…A cutoff AHI of ˂ 2/hr was utilized in most of these studies to define the absence of OSA, while 2.0-4.9/hr is often used to define mild OSA, 5.0-9.9 to define moderate OSA, and ˃10/hr to define severe OSA. Descriptively, across these child studies 21.5% of children had mild OSA (95% CI: 16.7 to 26.7), 20.3% moderate OSA (17.3 to 23.5), and 30.4% had severe OSA (20.5 to 41.2) [3], [6], [59], [62], [63], [65], [66], [68], [70], [76], [77]. All but two of these 11 child studies used an AHI cutoff of 2/hr for diagnosing OSA [11], [76].…”
Section: Prevalence Of Osa and Potential Moderatorsmentioning
confidence: 92%
“…Our results demonstrate that despite these children having significant improvements in OSA severity following surgery, approximately 50% have residual disease that is moderate/severe. from 16% to 66% 3,[12][13][14][15][16][17] ; these previous outcome data were based on relatively small cohorts of patients, ranging from 3 to 36 in sample size. Thottam and colleagues published the largest series to date, at 36 children, and they found that tonsillectomy (TO) decreased OSA severity, although only 16% of patients experienced complete resolution (OAHI < 1 event/h).…”
Section: Success Of Tonsillectomy For Obstructive Sleep Apnea In Chilmentioning
confidence: 99%
“…[1][2][3] Obstructive sleep apnea (OSA) is especially common in this population because of a combination of factors: macroglossia, hypotonia, increased prevalence of obesity, and craniofacial anatomy. Identification and treatment of OSA is important because it has been implicated as a contributing factor to pulmonary hypertension 1 as well as behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Врожденные пороки сердца и легочная гипоплазия, нередко наблюдаемые у детей с синдромом Дауна, могут дополнительно способствовать гипоксии в ночное время. Примечательно, что дети с синдромом Дауна, имеющие явные симптомы нарушений сна, характеризуются более выраженными психологическими отклонениями по срав-нению с теми, у которых нарушения сна выражены не сильно [33,34].…”
Section: вопросы современной педиатрииunclassified